Temperature increase altered Daphnia community structure in artificially heated lakes: a potential scenario for a warmer future - Dziuba, Marcin; Herdegen‑Radwan, Magdalena; Pluta, Estera; Wejnerowski, Łukasz; Szczuciński, Witold; Cerbin, Sławek (Springer Nature, 2020)
Under conditions of global warming, organisms are expected to track their thermal preferences, invading new habitats at higher latitudes and altitudes and altering the structure of local communities. To fend off potential invaders, indigenous communities/populations will have to rapidly adapt to the increase in temperature. In this study, we tested if decades of artificial water heating changed the structure of communities and populations of the Daphnia longispina species complex. We compared the species composition of contemporary Daphnia communities inhabiting five lakes heated by power plants and four non-heated control lakes. The heated lakes are ca. 3–4 °C warmer, as all lakes are expected to be by 2100 according to climate change forecasts. We also genotyped subfossil resting eggs to describe past shifts in Daphnia community structure that were induced by lake heating. Both approaches revealed a rapid replacement of indigenous D. longispina and D. cucullata by invader D. galeata immediately after the onset of heating, followed by a gradual recovery of the D. cucullata population. Our findings clearly indicate that, in response to global warming, community restructuring may occur faster than evolutionary adaptation. The eventual recolonisation by D. cucullata indicates that adaptation to novel conditions can be time-lagged, and suggests that the long-term consequences of ecosystem disturbance may differ from short-term observations.
Keywords: climate change; lake ecosystem; lakes; lake sediments; Daphnia; climate scenario; global warming; ecosystem disturbance; recolonisation; climate adaptation; sediment dating; 210Pb; 137Cs; resting eggs